Ecumenism and Independency in World Christianity : Historical Studies in Honour of Brian Stanley - Chow, Alexander; Wild-Wood, Emma (Theology and Mission in World Christianity, 2020)
'Ecumenism' and 'independency' suggest two distinct impulses in the history of Christianity: the desire for unity, co-operation, connectivity, and shared belief and practice, and the impulse for distinction, plurality, and contextual translation. Yet ecumenism and independency are better understood as existing in critical tension with one another. They provide a way of examining changes in World Christianity. Taking their lead from the internationally acclaimed research of Brian Stanley, in whose honour this book is published, contributors examine the entangled nature of ecumenism and independency in the modern global history of Christianity. They show how the scrutiny afforded by the attention to local, contextual approaches to Christianity outside the western world, may inform and enrich the attention to transnational connectivity.